Evaluation of global reanalysis winds and high‐resolution regional model outputs with the 205 MHz stratosphere–troposphere wind profiler radar observations. (26th April 2021) - Sivan, C.; Rakesh, V.; Abhilash, S.; Mohanakumar, K.
Abstract: A stratosphere–troposphere (ST) wind profiler radar operating at a high VHF range (205 MHz) installed at Cochin (10.03°N, 76.33°E), India, provides high‐resolution winds in time and altitude extending from 315 m to 20 km. We evaluated the horizontal and vertical winds obtained from atmospheric global reanalyses (ERA5, ERA‐Interim, MERRA‐2 and NCEP) data and the high‐resolution regional model (WRF) output winds with the ST radar (STR) wind observations at Cochin. The data for one whole year, from 1 August 2018 to 31 July 2019, for 0600 UTC and 1200 UTC were used. Wind data appraisal has been carried out at 24 levels from 315 m to 18.5 km altitude for the reanalyses datasets and 29 levels for model‐simulated winds in different seasons. Vertical profiles of horizontal winds from reanalysis and model‐simulated data somewhat catch the major changes observed from STR. The zonal winds match very well with the STR, whereas meridional winds show moderate similarity. Higher correlations in zonal winds are found during the summer monsoon, whereas meridional winds show apparent likeness during winter. The ERA5, ERA‐Interim, and model‐simulated winds have better agreement with the STR winds. Observed vertical winds from STR displays large fluctuations, while the estimated vertical winds in reanalysis are highly smoothed. Vertical profiles of vertical winds from the reanalysis datasets are not uniform. The reliability of vertical winds in reanalysis and WRF model output values are dubious compared to that of the directly observed winds from STR. The study indicates that improved quality of vertical and meridional winds in reanalysis data is needed by assimilating directly observed data from the available advanced facilities. Abstract : Assessment of the horizontal and vertical winds in global reanalysis and WRF model output, with the observed winds from ST radar in the tropics, is carried out. Reanalyses and model values precisely captured the high zonal winds, but meridional wind deviates from the observed winds. The reliability of vertical winds in reanalysis and WRF model output values are dubious compared to that of the directly observed winds from radar. Improved quality of vertical and meridional winds in reanalysis data is needed.